IMPLICATIONS OF CATASTROPHIC RISK FUTURE AS ALTERNATIVE RISKS TRANSFER SOLUTION ON PERFORMANCE OF MANUFACTURING COMPANIES IN NIGERIA - Moses Tunde Oyerinde; Adekunle Sunday Aduloju; Yusuf Olalekan Tajudeen (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
The manufacturing companies are faced with many risks which includes regular business risks such as credit risks, switch in market taste, human and personnel risks, injury, damage to third party and so on. The industry handles these risks by way of risk transfer through insurance by shifting the financial implication of loss, injury or damage to another party or parties.  However, there are risks that are existential to the industry that can be described as catastrophic such as hurricane, earthquake, terror attacks etc. These type of risks cannot be adequately covered by regular insurance. This class of risks can only be covered by non-insurance transfer by way of Alternative Risk Transfer, ART. The study aim to determine impact of Catastrophic Risk futures (CRF) as an alternative risks transfer solutions on the performance of Nigeria manufacturing companies revealed significant correlation between CRF as an ART solution and performance with correlation coefficient (r) of 0.630 with a p-value of 0.000. The ANOVA findings also showed performance of manufacturing enterprises could be strongly be predicted by CRF as well as a positive association between CRF solution and performance of the manufacturing companies. Therefore, we can conclude that there is significant relationship between CRF as an ART solution and the performance of Nigeria manufacturing companies and that CRF do have real impact on the performance of the manufacturing concerns. However, stakeholders such as the Government, the Manufacturers Association of Nigeria (MAN) and Security and Exchange Commission, SEC needs to work together to create enabling environment for ART to thrive by sensitization of the industry on the concept and benefits of ART. The industry must ensure that all alternative risk transfer solutions comply with local and international regulatory standards to avoid legal complications and ensure growth of the ART solutions in the country..